Final answer:
To find an equation equivalent to 3x+6=4x+7, isolate x by subtracting 3x and 7 from both sides, yielding x = -1. Therefore, the two equations are equivalent as they result in the same solution for x.
Step-by-step explanation:
The equation 3x+6=4x+7 can be solved by isolating the variable x. To find an equivalent equation, you can move terms involving x to one side and constant terms to the other side. Follow these steps:
- Subtract 3x from both sides of the equation to get: 6 = x + 7.
- Then, subtract 7 from both sides of the equation to isolate x: x = -1.
This shows that the value of x that satisfies both equations is x = -1. Thus, both equations are equivalent because they have the same solution.